Erosive wear of 446SS ferritic steel: a potential material for heat exchangers application. (31st August 2018) - Mishra, Ankitendran; Behera, C K; Mohan, S; Mohan, A
Abstract: In the present study, the effect of microstructure on the erosion of AISI 446 Stainless Steel is investigated under ambient conditions and elevated temperature conditions using erosion test rig similar to that shown in ASTM G76–95 standard. Various operating conditions with a discharge rate of 4.2 ± 0.5 gm min −1 and particle velocity of 100 m s −1 were employed at impact angles of 30°, 60°, and 90°. Micro-hardness test carried out for the sectioned eroded sample indicates the hardening effect along the cross-sectional depth, which inversely affects the erosion rate. It was found in agreement with previous theories that 446SS showed higher erosion resistance at normal impact than oblique impacts in case of ambient conditions, whereas, under elevated temperature conditions increasing trend in erosion was seen. Surface and sub-surface examinations were carried out using SEM, 3D-profilometer, and surface roughness analyzer. Ploughing, metal cutting, indentation and crater formation are the mechanisms primarily responsible for erosion, indicating severe erosion at 30° impact angle. It was also observed that under high temperature working conditions dissolution of carbides precipitates occurs which affects the mechanical properties of the material.